Research of Warm Acupuncture at Shu and Mu Acupoints Combined with Bladder Functional Training in the Treatment of Spasm Type of Neurogenic Bladder after Spinal Cord Injury - Shijie HAO; Hongyan BI; Zhenmei GAO (康复学报)
Objective:To observe the clinical efficacy of warm acupuncture at Shu and Mu acupoints combined with bladder functional training in the treatment of spasm type of neurogenic bladder after spinal cord injury (SCI).Methods:A total of ninety patients with spasm type of neurogenic bladder after incomplete SCI were randomly assigned to the bladder functional training group, the warm acupuncture group, and the treatment group (warm acupuncture at Shu and Mu acupoints combined with bladder functional training group), each group of 30 cases. On the basis of three groups in basic medical treatments, each group received corresponding treatments for once a day and one month as a course. After three courses of treatment, the changes of bladder capacity, residual urine volume, bladder pressure and life quality scores of three groups were observed.Results:Three months after treatment, the bladder capacity of three groups were increased, and the treatment group is more obvious than the other two groups (P<0.05), the residual urine volume and bladder pressure of three groups decreased significantly, and the quality of life scores improved significantly, the treatment group changed more obviously than the other two groups (P<0.05).Conclusion:Warm acupuncture at Shu and Mu acupoints combined with bladder functional training could improve the bladder function in patients with neurogenic bladder after SCI, and the combination of curative efficacy is more significant.